2018
DOI: 10.1002/ccd.27913
|View full text |Cite
|
Sign up to set email alerts
|

Favorable neurological outcome after ischemic cerebrovascular events in patients treated with percutaneous left atrial appendage occlusion compared with warfarin

Abstract: Objectives This study sought to investigate neurological disability after ischemic cerebrovascular events in patients treated with left atrial appendage (LAA) occlusion compared with those on warfarin. Background Prior studies demonstrated that cerebrovascular events after LAA occlusion in patients with nonvalvular atrial fibrillation (NVAF) is largely nondisabling. Methods From the 1,189 patients in the Korean LAA Occlusion and European Amplatzer Cardiac Plug Multi‐Center Registry, 24 patients who experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…7)9) More recently, we reported that NVAF patients previously treated with LAAO experienced more favorable outcomes following ischemic cerebrovascular events than patients taking warfarin. 8) The prevalence of disabling ischemic…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7)9) More recently, we reported that NVAF patients previously treated with LAAO experienced more favorable outcomes following ischemic cerebrovascular events than patients taking warfarin. 8) The prevalence of disabling ischemic…”
Section: Discussionmentioning
confidence: 99%
“…6) Recent studies have reported less disabling and lethal strokes after percutaneous LAAO with the Amplatzer cardiac plug (ACP; Abbott Vascular, St. Paul, MN, USA) or Watchman device (Boston Scientific, Marlborough, MA, USA) than those in patients on warfarin therapy. [7][8][9] However, no comparative data regarding ischemic cerebrovascular eventassociated neurological outcomes following percutaneous LAA closure or NOAC treatment are…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Moreover, patients who experienced ischemic cerebrovascular events during follow-up had more favorable neurological and functional outcomes if treated with LAAO compared with those treated with warfarin. 33 Furthermore, in patients with CKD treated with LAAO, even in those with eGFR less than 15 ml/min/1.73 m 2 , a significant reduction of almost 60% was observed in stroke/TIA rate and major bleeding rate in comparison with the expected annual risk. 34 Another critical aspect in the area of atrial fibrillation treatment is the adherence to anticoagulant agents.…”
Section: Discussionmentioning
confidence: 96%
“…It is conceivable that patients with prior stroke may benefit more from LAAC in decreasing stroke recurrence than those without prior stroke. This could be because patients with AF who underwent LAAC exhibited a significantly reduced risk of disabling cerebrovascular outcome after ischemic cerebrovascular events in contrast to oral warfarin treatment ( 28 ), and LAAC delivered more quality-adjusted life years as well as more cost-effectiveness relative to NOACs for secondary prevention of stroke in AF patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%